2021
DOI: 10.1016/j.chempr.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

A unified topology approach to dot-, rod-, and sheet-MOFs

Abstract: We offer insights into how network topology influences stability of metal-organic frameworks and suggest the application of rare sheet-MOFs, where metal ions and linkers form infinite 2D units (SBUs) as a strategy for achieving higher stability. We also demonstrate a unified topology approach to MOFs exemplified by the dot-, rod-, and sheet-MOFs reported. These MOFs are based on vicinal dicarboxylates, which we propose as a way to prepare rod-MOFs. Cyclic voltammetry suggests Ce(IV)-MOFs as being more stable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 90 publications
1
30
0
Order By: Relevance
“…Besides, ISBU MOFs based on transition metals( iii ) have also been prevailingly studied. 21,31,97–100 The recently emerged CAU-50 (ref. 99) [Sc 2 (FcDC) 3 ] was a 1D Sc-MOF constructed by reacting Sc(NO 3 ) 3 ·5H 2 O with H 2 FcDC in a mixture of water and DMF at 95 °C.…”
Section: Isbu Mofsmentioning
confidence: 99%
See 4 more Smart Citations
“…Besides, ISBU MOFs based on transition metals( iii ) have also been prevailingly studied. 21,31,97–100 The recently emerged CAU-50 (ref. 99) [Sc 2 (FcDC) 3 ] was a 1D Sc-MOF constructed by reacting Sc(NO 3 ) 3 ·5H 2 O with H 2 FcDC in a mixture of water and DMF at 95 °C.…”
Section: Isbu Mofsmentioning
confidence: 99%
“…12f). Öhrström et al 21 reported a type of 1D Gd-MOF from the reaction of Gd(NO 3 ) 3 ·6H 2 O with benzene-1,2,4,5-tetracarboxylate (H 4 BTEC), 4,4′-azopyridine in a mixture of DMF and acetic acid. The central Gd 3+ among the obtained CTH-16 [Gd 2 (BTEC) 2 ] was coordinated by nine carboxylate oxygens from six different BTEC ligands (Fig.…”
Section: Isbu Mofsmentioning
confidence: 99%
See 3 more Smart Citations